Strategi Mengurangi Stigma Penyakit Kusta di Komunitas - Koko Wahyu Tarnoto; Junaiti Sahar (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: The impact of the stigma caused people with leprosy not only suffer physically but also psychologically because they were isolated and ignored by family members and the surrounding community. Aims this study is to describe strategy to decrease stigma for leprae patient. Methods: The type of research design included in the literature review. The studies will be reviewed in English using qualitative, quantitative, and mixed methods. Searches were carried out using Science direct, PubMed (Medline), Google Search and Proquest with keywords for each variable. Keywords in leprosy search, AND (Stigma or discrimination) AND (Intervention or IEC or counseling). Results: The stigma is explained in five categories, namely the integration of leprosy services into health care, communication, information and education programs, socio-economic rehabilitation, change in name of leprosy, and counseling. Conclusion: The interventions carried out provide at least evidence of success in efforts to deal with stigma with various strategies, namely the integration of leprosy programs into health care, IEC and SER interventions.